Assessment of Health Management Information System (HMIS) perfomance in health facilities in Mbarali, Kyela, and Busokelo District Councils - Sanga, Jactany L. (Mzumbe University, 2026)
Report submitted in partial fulfillment of the requirements for Degree of Master of Science in Health Monitoring and Evaluation (M.Sc. HME) of Mzumbe University